Age and CYP3A5 genotype affect tacrolimus dosing requirements after transplant in pediatric heart recipients - Gijsen, Violette (2011)
BACKGROUND: Tacrolimus is one of the commonly used immunosuppressive drugs for pediatric heart transplants. Large variation exists in pharmacokinetics during the direct post-transplant period, resulting in an increased risk of adverse events. Limited data are available on the interaction of age, CYP3A5 and ABCB1 genotype, and disease severity on the variation in disposition and outcome in pediatric heart transplant recipients. METHOD: We studied the relationship between age and CYP3A5 and ABCB1 genotype and the Pediatric Risk of Mortality (PRISM) score on tacrolimus dose (mg/kg), steady-state trough concentrations, and concentration/dose ratio, as well as rejection and renal function for 14 days after heart transplant in children. RESULTS: Tacrolimus was administered to 39 children (median age, 6.0 years) after transplant. A correlation was found between the age at the time of transplant and the tacrolimus dosing requirements (r(s) = −0.447, p = 0.004) and the concentration/dose ratio (r(s) = 0.351, p = 0.029). CYP3A5 expressors required median (interquartile range) higher doses of tacrolimus (0.14 [0.09] vs 0.06 [0.04] mg/kg/12 hours, p = 0.001), and had lower concentration/dose ratios (45.34 [44.54] vs 177.78 [145.38] ng/ml per mg/kg/12 hours, p < 0.0001). This relationship was not seen with the ABCB1 genotype. Age and CYP3A5 genotype predicted the tacrolimus dosing requirements as well as the concentration/dose ratio (R(2) = 0.351, p = 0.001 and R(2) = 0.521, p < 0.001). No relationship was found between any of the CYP3A5 or ABCB1 genotypes and the estimated glomerular filtration rate. CONCLUSION: Younger age and CYP3A5 expressor genotype were independently associated with higher dosing requirements and lower tacrolimus concentration/dose ratios.